On the independence of Matthew and Mark - Rist, John (Society for New Testament Studies monograph series, 1978)
It has for long been generally assumed that the relationship between our canonical texts of the Gospels of Mark and Matthew is to be explained in terms of direct literary dependence, either of Matthew on Mark, or of Mark on Matthew. Professor Rist questions this assumption vigourously, and argues that it leads to contradictory and paradoxical conclusions. He replaces the theory of literary dependence with the thesis that Matthew and Mark grew up independently on the basis of a common oral tradition, and supports his view by detailed examination of a large number of parallel passages. The clarity and cogency of the author's argument is in the best tradition of this important series of monographs. In the context of the current resurgence of interest in the Synoptic problem, it will be welcomed by all concerned with the study of the New Testament.